2020
DOI: 10.3390/w12041042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Farming Practices and Land Use on Groundwater Resources in a Coastal Multi-Aquifer System in Puck Region (Northern Poland)

Abstract: This study focuses on the modeling of groundwater flow and nitrate transport in a multi-aquifer hydrosystem in northern Poland, adjacent to Puck Bay (Baltic sea). The main goal was to investigate how changes in land use and farming practices may affect groundwater recharge and submarine groundwater discharge (SGD) to the sea and the associated N-NO3 fluxes. An integrated modelling approach has been developed, which couples the SWAT hydrologic model, MODFLOW-NWT groundwater flow model, and MT3DMS transport mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Virtasalo et al (2019) observed the melted spots on the sea ice along the shoreline during spring, which could be caused by the discharge of warmer groundwater (average temperature of 7°C). A similar situation was described by Szymkiewicz et al (2020), where the rate of SGD varies seasonally and in relation to recharge, with peaks in late winter to early spring. In this study, the measurement of EC and temperature at the sea bottom along the shoreline was carried out in summer when the groundwater level and recharge are low.…”
Section: Discussionsupporting
confidence: 67%
“…Virtasalo et al (2019) observed the melted spots on the sea ice along the shoreline during spring, which could be caused by the discharge of warmer groundwater (average temperature of 7°C). A similar situation was described by Szymkiewicz et al (2020), where the rate of SGD varies seasonally and in relation to recharge, with peaks in late winter to early spring. In this study, the measurement of EC and temperature at the sea bottom along the shoreline was carried out in summer when the groundwater level and recharge are low.…”
Section: Discussionsupporting
confidence: 67%
“…Due to the lack of sufficient data on stream discharge, it was decided to perform calibration by a manual trial-and-error procedure ( Szymkiewicz et al, 2020 ). For calibration, meteorological data from the years 2000–2009 were used.…”
Section: Methodsmentioning
confidence: 99%
“…The results quoted here refer to the current conditions of land use and agricultural practices as obtained from the survey of Puck area. Modelling studies showed that changes in land use and agricultural practices have considerable influence on groundwater flow rates and nitrate loads at the land-sea interface [6].…”
Section: Groundwater Dischargementioning
confidence: 99%
“…• two calculators for farms in the Puck Commune as an interactive applications [4,5], • a numerical model of groundwater flow based on Modflow [6], • a comprehensive model of surface water runoff based on Soil & Water Assessment Tool (SWAT) [7], • a three-dimensional numerical model of the Puck Bay ecosystem consisting of a hydrodynamic [1] and biochemical part with a nutrient spread module (this paper).…”
Section: Introductionmentioning
confidence: 99%